Design, in silico and pharmacological evaluation of a peptide inhibitor of BACE-1 - Boldin, Renata; Zychar, Bianca Cestari; Gonçalves, Luis Roberto C.; Sciani, Juliana Mozer (Frontiers in Pharmacology, 2023)
Alzheimer's disease (AD) is the main type of dementia, caused by the accumulation of amyloid plaques, formed by amyloid peptides after being processed from APP by γ- and β-secretases (BACE-1). Although amyloid peptides have been well established for AD, they have been found in other neurodegenerative diseases, such as Parkinson’s Disease, Lewy body dementia, and amyotrophic lateral sclerosis. Inhibitors of BACE-1 have been searched and developed, but clinical trials failed due to lack of efficacy or toxicity. Nevertheless, it is still considered a good therapeutic target, as it was proven to remove amyloid peptides and to improve memory. In this work we designed a peptide based on a sequence obtained from the marine fish Merluccius productus and evaluated it by molecular docking to verify its binding to BACE-1, which was tested experimentally by enzymatic kinetics and cell culture assay. The peptide was injected in healthy mice to study its pharmacokinetics and toxicity. We could obtain a new sequence, in which the first N-terminal amino acids and the last one bound to the catalytic site of BACE-1 and showed high stability and hydrophobicity. The synthetic peptide showed a competitive inhibition of BACE-1 and Ki = 94 nM, and when injected in differentiated neurons, could reduce the Aβ42o production. In plasma, its half-life is ~1 h, clearance and Vss 0.0015 µg/L/h. The peptide was found in spleen and liver 30 minutes after injection and reduced its level after that, when was quantified in the kidneys, indicating its fast distribution and urinary excretion. Interestingly, the peptide was found in the brain 2 h after its administration. Histological analysis showed no morphological alteration in any organ, as well as the absence of inflammatory cells, indicating lack of toxicity. In conclusion, we obtained a new BACE-1 inhibitor peptide with fast distribution to the tissues, without accumulation in any organ, but found in the brain, with possibility to reach its molecular target, BACE-1, contributing to the reduction of amyloid peptide, which cause amyloid-linked neurodegenerative diseases.